Panax ginseng for Frailty-Related Disorders: A Review - Ogawa-Ochiai, Keiko; Kawasaki, Kanji (Frontiers in Nutrition, 2019)
This review aims to understand the clinical efficacy of Panax ginseng (PG) for managing frailty-related disorders by reviewing meta-analyses, systematic reviews, and randomized clinical trial data. PG is widely used in traditional medicine, mainly in East Asia. It has traditionally been indicated for the collapse of qi or for abandoned conditions that manifest as shallow breathing, shortness of breath, cold limbs, profuse sweating, a low pulse rate, or weakness. In accordance with these indications, PG is used for managing conditions such as aging, inflammation, and cancer. PG is also used in some functional foods or supplements. Some studies have shown the effects of ginsenosides, which are the major constituents of PG. With regard to pharmacological activities of ginseng saponins, it has been presumed that these ginsenosides are metabolized into active forms by human intestinal microbiota after being taken orally. Therefore, we focused on reviewing the data of clinical studies on PG. Although there has been no study that directly investigated the effect of PG on frailty, a number of clinical studies have been conducted to investigate the efficacy and safety of PG and its interactions with other modern ginseng medications and ginseng-containing formulas. We searched the randomized controlled trial data from 1995 to 2018 and reviewed the potential effects of PG on frailty-related disordersfrailty. We reviewed the effects of PG on glucose metabolism, fatigue, hypertension, cardiovascular disorders, chronic obstructive pulmonary disease, renal function, cognitive function, and immune function. Our review showed some evidence for the usefulness of ginseng, which suggests that it has the potential to be used for the management of aging-related and frailty symptoms, such as fatigue and hypertension, although most of the studies we evaluated were conducted in middle-aged adults. However, age-related changes in microbiota may influence the effect of PG since some studies suggest that ginsenosides are prodrugs that are activated in the body upon deglycosylation by intestinal bacteria and esterification with fatty acids. Further investigation of the clinical use of PG in elderly patients should be conducted.